Wandering in the Realm of History Experimenting with Pedagogy - Falari, Bharati Prashant (JOURNAL OF INDIAN EDUCATION, 2019)
Teaching history to the D.El.Ed trainees is both, a challenge and an opportunity. The huge burden of ‘accumulated facts’ (that is, what we transform history into) could be reduced considerably by introducing innovative ideas and initiating a culture of collaborative learning. The relationship between the past, present and future can be effectively transacted through vivid activities related to the social milieu and personal experience of the learners. This article explores the journey of the author (a teacher educator in history and civics) and her teacher-trainees into the pedagogy of the subject, and the possibilities of creative and collaborative learning as introduced by DIET, Goa.